Phytoplankton Community Structure in Bun-Bun River Waters, Kubu Raya Regency, West Kalimantan - Uci Ramadhani; Entin Daningsih; Wolly Candramila (Quagga: Jurnal Pendidikan dan Biologi, 2024)
The Bun-bun River was located in a mangrove forest area in Kubu Raya Regency and empties into the sea. As the main producers at the trophic level of waters, phytoplankton has an important role in assessing river quality. This study aims to find out phytoplankton community structure including abundance, diversity, uniformity, and dominance indexs in relation to Bun-bun River quality. The observations were made in the dry and rainy seasons at three stations starting from the initial end of the mangrove forest (Station 1), the middle (Station 2), and the final end which also empties into the sea (Station 3). Sampling was carried out at three points (left edge, center, right edge). Measurements of physico-chemical factors include brightness, current velocity, temperature, pH, DO, dissolved CO2, salinity, nitrate and phosphate. Phytoplankton sampling used a 30 µm plankton net mesh size and identification down to the species level. The calculated index values include abundance, diversity, uniformity, and dominance. The Bun-bun River was characterized by brackish waters with calm surface currents (<0.1 m.s-1) and a salinity between 5.4-9.48 ppt. Dissolved CO2 levels are relatively high, namely 22-30.8 mg.L-1 in the dry season and 35.2 mg.L-1 in the rainy season. During the dry season, the pH of the water becomes slightly acidic (6.51-6.76) and relatively neutral during the rainy season (7.08-7.52). Nitrate and phosphate levels were low in both seasons and all three stations. The brightness of the water was higher in the dry season than in the rainy season (20-44 cm). A total of 52 types of phytoplankton were found belonging to four classes, namely Class Bacillariophyceae (25 species), Dinophyceae (14), Chlorophyceae (12), and Chrysophyceae (1). Phytoplankton abundance index was low to moderate. The diversity index was moderate at almost all stations except for the low at Station 3 in the rainy season. The uniformity index at Station 3 was low in the dry season but high in the rainy season, and moderate in other locations. The dominance index was high at Station 3 during the dry season and moderate at other locations. Physico-chemical factors such as salinity, dissolved CO2, nitrate and phosphate levels are most likely to influence abundance, while diversity was influenced by dominance.